Studi Empiris Faktor Determinan Financial Distress - Maria Purwantini; Rahmawati Hanny Yustrianthe; Budhi Purwantoro Jati; Ani Sri Murwani (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of profitability, liquidity, leverage, sales growth, and company size on financial distress in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Profitability is proxied by Return on Assets (ROA), liquidity is proxied by the current ratio (CR), leverage is proxied by Debt to Total Equity (DER). The population used in this study are all mining companies listed on the IDX. The sample selection in this study used a purposive sampling method and obtained 22 companies. The analysis used is multiple linear regression. The results of this study indicate that profitability, liquidity and leverage have a significant effect on financial distress. Meanwhile, sales growth and company size have no effect on financial distress.